PLANTING CORALS SEBAGAI UPAYA MENDUKUNG PENGEMBANGAN EKOWISATA BAHARI BERBASIS SUSTAINABLE TOURISM DI PANTAI PANDAWA - Mella Manika Surya Dewi, Ni Kadek; Eka Sudarmawan, I Wayan; Arun Suwi Arianty, A. A. Ayu; Eka Susanti, Luh (CV. Lafadz Jaya, 2024)
Coral reefs have a mutual advantage between organisms and their environment. It contains enormous and various benefits, both ecologically and economically. Pandawa Beach is one of the beaches in Bali which is very beautiful and has a very high potential for marine ecotourism. There are many activities that can be done and are able to preserve marine ecosystems. One of them is planting corals which aims to build a cultivated coral reef garden area by involving tourists in the hope of being able to preserve nature, increase tourist visits, educate tourists, develop tourism and make Pandawa Beach a coral canter. In addition, efforts are also made to become a sustainable tourism business by preserving nature and increasing education in the field of marine ecotourism, especially coral reef ecosystems. The research method used is a qualitative approach through observation, interviews and collecting documentation during the activity, then described descriptively. Planting corals activities are able to maintain and preserve coral reef ecosystems, develop marine ecotourism and really help develop sustainable tourism, as well as helping the economy of the surrounding community by increasing tourist visits from disseminating information carried out by tourists carrying out planting corals activities on social media.